EXTRATO DA CASCA DE PERSEA PYRIFOLIA COMO INIBIDOR DE CORROSÃO DO AÇO CARBONO 1020 - Vieira, Carine (2020)
Carbon steel is one of the most used alloys in industrial applications due to its low cost when compared to other alloys and its mechanical properties. However, its use may be limited due to its tendency to corrosion. Thus, it is necessary to develop methods that inhibit its degradation. One way to reduce corrosion is through the use of corrosion inhibitors, which are generally organic compounds and can act by adsorption to form protective films. Some organic compounds with hetero atoms like O, N, S inhibit corrosion by forming a protective film. However, the use of some inhibitors has been limited due to their properties being harmful to the environment. For this reason research has been developed looking for ecologically correct corrosion inhibitors, an alternative to replace inhibitors of synthetic origin, often toxic, is the use of natural inhibitors. These corrosion inhibitors are found in different plant extracts. In the present work, an aqueous and ethanolic extract from the bark of the Persea pyrifolia (PP) plant was used in order to evaluate the inhibitory effect of the PP bark extract against the corrosion of 1020 carbon steel in contact with the electrolytic solutions of NaCl 0,5 mol L-1 and 0,1 mol L-1 HCl. The carbon steel plates were immersed in the aqueous extract and in the ethanolic extract of the PP plant bark in concentrations of 2,5% V / V, 5% V / V and 10% V / V with an initial mass of PP of 120 g 40 g. In addition, tests were performed with time variation of up to 120 h of immersion in the aqueous extract. The electrochemical characterization of the samples was performed by open circuit potential (ECA), anodic potentiodynamic polarization (PPA) and electrochemical impedance spectroscopy (EIS). In addition, mass loss was measured and inhibitory efficiency was assessed. The plates were characterized by scanning electron microscopy (SEM) and dispersive energy spectroscopy (EDS). Electrochemical analyzes indicated protection against corrosion in aqueous extract. In the presence of 0,5 mol L-1 NaCl electrolyte, the best result found was for the concentration of 10% V / V, for which a 73% coverage level was obtained. In the presence of the HCl 0,1 mol L-1 electrolyte the best result found was for the concentration of 2,5% V / V with a coverage degree of 82,5%.